1980
DOI: 10.1021/ma60077a014
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Copolymers of Isobutylene. 3. Nuclear Magnetic Resonance Investigation of the Structure of Isobutylene-trans-1,3-Pentadiene Copolymer

Abstract: The base frequencies used for calculation were vCH" = 29.90 and IB-Ip copolymers containing high amounts of IP, i.e., >50 ppm (resonance of linear polyethylene) and vc = 33.00 ppm mol %. (quaternary carbon of the gem-dimethyl group present in a (21) Regular enchainment means in the context the essential polymethylene chain).head-to-tail insertion of the monomers. They arise from the (20) Units arising from the opening of the 3,4 double bond of Ip 1,2-IB addition and trans-1,4 (not tians-4,1) IP addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“… a Observed data taken from ref ; calculated intensities analyzed via the program PERTEMG. b Feed, f A = 0.500 and conversion = 6.6%.…”
Section: Examples Of Perturbed Model With Emg Functionmentioning
confidence: 99%
See 1 more Smart Citation
“… a Observed data taken from ref ; calculated intensities analyzed via the program PERTEMG. b Feed, f A = 0.500 and conversion = 6.6%.…”
Section: Examples Of Perturbed Model With Emg Functionmentioning
confidence: 99%
“…Isobutylene/Isoprene Copolymers. Corno et al 38 have copolymerized isobutylene and isoprene using cationic means. They made several samples at different conversions and different comonomer feed ratios and obtained the triad intensities from both 1 H and 13 C NMR spectra.…”
Section: Examples Of Perturbed Model With Emg Functionmentioning
confidence: 99%
“…Isobutene is regarded as a monomer for cationic polymerization and for cationic copolymerization with styrene and dienes. The coordination polymerization of such 1,1-disubstituted olefins is rare because of the steric hindrance between the polymer end and the new monomer. Very recently, neutral palladium complexes with phosphine–sulfonate ligand systems have been reported to copolymerize ethylene and 1,1-disubstituted olefins having functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been some reports about the cationic copolymer of PD with other monomers, such as olefin, styrene [4][5][6][7][8][9][10][11], research in the cationic copolymerization of PD with AP has rarely been reported. We are interested in the cationic PD-AP copolymerization because it is of significance for synthesis of the copolymer with high softening point and light color.…”
Section: Introductionmentioning
confidence: 99%